Resiliensi Bisnis UMKM Produk Olahan Ikan selama Masa Pandemi: Peluang dan Kendala - Vembri Aulia Rahmi; Sudarmiatin Sudarmiatin (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2022)
Indonesia's marine potential is an asset for community livelihoods and business prospects for fish processing in coastal areas. One of them is UD. Barokah as an MSME in the field of selling high quality fish and diversifying the business of selling fish crackers with business partners in other cities. This study aims to explore how business resilience is in coastal entrepreneurs by analyzing opportunities and constraints in business continuity during the pandemic. This research design uses an exploratory qualitative approach. Data collection, through: semi-structured interviews with UD owners and managers. blessing. Semi-structured interviews by asking structured questions and have been prepared as a guide to find problems. Possible interview questions differ from the script, but according to the context of the topic of discussion. The results of this study stated that during the UD. Barokah experienced a surge in sales turnover. Business opportunities made from marine fish are supported by the ability of business managers to drive business. UD's business constraints. The blessing during the pandemic is the limited production of crackers, due to the scarcity of supply of good quality fish due to weather factors Indonesian.